Case Report: Allergic Reactivity to Mahaleb (Prunus mahaleb) Spice in a Subject With Almond and Other Tree Nut Allergies. (September 2020) - Benoit, Lora; Masiri, Jongkit; Janagama, Harish; Gendel, Steven M.; Samadpour, Mansour
Background: Mahaleb is an aromatic spice prepared from the fruit stone of the St. Lucie Cherry that is used as a flavoring agent in traditional Turkish and Middle Eastern baking. Immunodiagnostic kits for almond, which are based on polyclonal almond-specific IgG antibodies, have been shown to demonstrate considerable cross-reactivity with mahaleb as was incidentally discovered during a cluster of allergen-related food recalls in 2015. Objective: Though acute allergy to almond is somewhat common, allergies to mahaleb have not been previously documented. However, based on antigenic similarity observed with almond-specific IgG, it is predicted that mahaleb nut proteins would exhibit some level of cross-reactivity with almond-specific IgE and may therefore potentiate acute allergic symptoms in individuals with food allergy to almond. Case Presentation: Herein, we report on a 40-year old Caucasian female with longitudinal history of multiple tree nut allergies including allergy to almond, presenting with moderate pruritus and oropharyngeal swelling shortly following ingestion of mahaleb seed kernels. Methods and Results: Skin-prick testing using extracts compounded from pistachio, almond, and mahaleb revealed positive wheals measuring 8, 3, and 7 mm respectfully. Indirect enzyme-linked immunosorbent assay (ELISA) using plate-bound antigens prepared from pistachio, almond, and mahaleb revealed IgG positive responses to all three targets. ELISA and Western blot analysis performed using goat anti-almond polyclonal IgG demonstrated significant cross-reactivity between almond and mahaleb, but not to pistachio. Conclusion: This is the first documented case of acute allergy to mahaleb, co-occurring in the context of plural tree nut allergies, providing novel evidence that mahaleb may pose a risk to nut-allergic individuals and indicating a need for awareness of spice contamination with nut and mahaleb residues.